Learning to be in a society with others: Inclusion and the role of after school programs like Hitt Húsið for youth with disabilities - Rosana Valle Tamés 1989- (2018)
Nowadays, mainstream schools are more and more mixed worldwide, and in the case of Iceland, less than 1% of students attend special schools. However, the integration into mainstream schools can often be superficial. This thesis reviews the status of inclusive education, paying special attention to the case of Iceland with a focus on the social context of inclusion and the importance of after school programs for people with disabilities. More precisely, this thesis focuses on an after school program for young people between 16 and 20 years old in Iceland called Hitt Húsið. Theoretical analysis is used to explain some key concepts, as well as one interview with the project manager of the after school program at Hitt Húsið. My conclusions suggest that as all forms of education should be about empowering individuals, there should be an emphasis on informal education in order to facilitate inclusion.